The effects of using semantic mapping strategy training on reading comprehension performance among UTHM students - Mohd Junaid, Thuwaibah (Science Publishing Corporation (SPC), 2018)
The objective of this study is to identify the effects of semantic mapping on the reading comprehension texts among University Tun Hussein Onn Malaysia (UTHM) degree students. This study sought to determine if there are any benefits in instructing UTHM students to use semantic mapping as a mean of improving their comprehension of information in reading texts. The effects will be measured by comparing the results of pre test and post test conducted among the students. The sample consisted of 40 UTHM degree students who were from one class. All of them received the semantic mapping strategy training and sat for both pre test and post test. The findings indicated that semantic mapping strategy training affected the reading comprehension performance among the students based on the differences in the students‟ results of pre test and post test. The results of this finding can be implied by educators in their teaching and learning process